2022
DOI: 10.3389/fonc.2022.946086
|View full text |Cite
|
Sign up to set email alerts
|

AMBRA1 and its role as a target for anticancer therapy

Abstract: The activating molecule in Beclin1-regulated autophagy protein 1 (AMBRA1) is an intrinsically disordered protein that regulates the survival and death of cancer cells by modulating autophagy. Although the roles of autophagy in cancer are controversial and context-dependent, inhibition of autophagy under some circumstances can be a useful strategy for cancer therapy. As AMBRA1 is a pivotal autophagy-associated protein, targeting AMBRA1 similarly may be an underlying strategy for cancer therapy. Emerging evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…AMBRA1 has been reported to have various functions in carcinogenesis, including autophagy, tumorigenesis, proliferation, and the cell cycle. Emerging evidence has indicated that AMBRA1 affects cancer formation, maintenance, and progression by regulating c-MYC and cyclins, which are frequently deregulated in human cancer cells [ 42 ]. CACNA1A is a protein in voltage-dependent Ca 2+ channels that controls the entry of Ca 2+ into excitable cells and regulates BP through vascular smooth muscle contraction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMBRA1 has been reported to have various functions in carcinogenesis, including autophagy, tumorigenesis, proliferation, and the cell cycle. Emerging evidence has indicated that AMBRA1 affects cancer formation, maintenance, and progression by regulating c-MYC and cyclins, which are frequently deregulated in human cancer cells [ 42 ]. CACNA1A is a protein in voltage-dependent Ca 2+ channels that controls the entry of Ca 2+ into excitable cells and regulates BP through vascular smooth muscle contraction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These reported regions locate at the intrinsically disordered regions linking WD40-N and WD40-C, and C-terminus. Furthermore, the N-terminal and C-terminal regions of AMBRA1 are involved in interaction with BCL-2, ULK1, ELONGIN B and PARKIN, however the precise interaction sites are not known [29]. In order to gain insights how these regions are organized relative to AMBRA1 WD40 domain in CRL4 structure, we superimposed the Alphafold2 model of AMBRA1 which retains all the loops to our CRL4-AMBRA1 structural model ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As well, AMBRA1 has a significant role in apoptosis as an autophagy-associated protein and a direct substrate for cystathionin and calpain ( Maria Fimia et al, 2007 ). During the stage of autophagy induction, AMBRA1 is capable of modulating ULK1 kinase activity, as well as interacting with BECLIN1 and VPS34 to manage relevant activities ( Li X. et al, 2022 ). Under normal conditions, AMBRA1 has a preference to interact with mitochondrial BCL-2 (mito-BCL-2), and when mitophagy is activated, the interaction between AMBRA1 and mito-BCL-2 is broken ( Strappazzon et al, 2011 ).…”
Section: Regulatory Signaling Pathways Of Mitophagymentioning
confidence: 99%